Effect of 1-methylcyclopropene and ethylene on the physiology of peach fruits (Prunus persica L.) cv. Dorado during storage - Mariño-González, Luz Amparo; Buitrago, Claudia Marcela; Balaguera Lopez, Helber Enrique; Martínez-Quintero, Efraín (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2019)
The peach (Prunus persica L., family Rosaceae) is a drupe that is consumed fresh and used in industry; it has a climacteric behavior and, because of its high water content, is highly perishable. This study aimed to evaluate the effect of 1-methylcyclopropene (1-MCP) and ethylene on the postharvest physiology of peach fruits cv. Dorado. Harvested fruits with 100% green, 0% yellow skin color were used in a completely randomized design with four treatments: ethylene, 1-MCP, 1-MCP+ethylene and a control. After treatment, the fruits were stored at room temperature. During storage, the respiration rate, weight loss, firmness, color index of the skin, total soluble solids, total acidity and maturity ratio were evaluated. The results showed the efficiency of 1-MCP in peach cv. Dorado: 1-MCP decreased the respiration rate, color index of the skin, soluble solids and maturity ratio, while the firmness and total acidity were greater. The ethylene application showed an opposite effect, suggesting that it may regulate a large part of peach cv. Dorado ripening.